2020
DOI: 10.1016/j.acra.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Volume Trends and Recovery During the COVID-19 Pandemic: A Comparative Analysis Between a Large Urban Academic Hospital and Its Affiliated Imaging Centers

Abstract: Rationale and Objectives: While affiliated imaging centers play an important role in healthcare systems, little is known of how their operations are impacted by the COVID-19 pandemic. Our goal was to investigate imaging volume trends during the pandemic at our large academic hospital compared to the affiliated imaging centers. Materials and Methods: This was a descriptive retrospective study of imaging volume from an academic hospital (main hospital campus) and its affiliated imaging centers from January 1 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 18 publications
(31 reference statements)
5
34
0
2
Order By: Relevance
“…As a result, complexity remained elevated throughout the system months after the outbreak peak. Similarly asymmetric changes between academic sites and nonacademic imaging centers were also previously reported from a large system in Massachusetts ( 22 ).…”
Section: Discussionsupporting
confidence: 76%
“…As a result, complexity remained elevated throughout the system months after the outbreak peak. Similarly asymmetric changes between academic sites and nonacademic imaging centers were also previously reported from a large system in Massachusetts ( 22 ).…”
Section: Discussionsupporting
confidence: 76%
“…Nuclear medicine has been one of the imaging modalities that exhibited the greatest degree of volume reduction during the COVID-19 pandemic [12,13,17,18]. In our study, we observed a reduction of around 43% in nuclear medicine examinations volume between the periods directly before and during the lockdown.…”
Section: Discussionsupporting
confidence: 53%
“… 1 Our prior research demonstrated hospital-wide overall volume decreases of 54–64%. 5 The authors speculate that the magnitude of decline in imaging volume is multifactorial - population density, patient catchment area, severity of COVID-19 outbreaks, and social distancing policies are a few of many possible factors.…”
Section: Discussionmentioning
confidence: 99%
“… 4 While recent studies on imaging volume in the context of the pandemic have highlighted absolute declines in imaging utilization and corresponding work relative value unit (wRVU) data, specific data on changes in per-patient utilization, including data by modality and corresponding wRVU, have not been reported. 5. , 6.…”
Section: Introductionmentioning
confidence: 99%